2009
DOI: 10.3354/esr00117
|View full text |Cite
|
Sign up to set email alerts
|

How many species of goliath grouper are there? Cryptic genetic divergence in a threatened marine fish and the resurrection of a geopolitical species

Abstract: The goliath grouper Epinephelus itajara (Epinephelidae) is an exceptionally large marine fish that inhabits sub-tropical and tropical waters of the Americas and western Africa. Due to a lack of readily observable morphological variation in specimens across its range, the goliath grouper has been regarded as a single species. We tested the hypothesis that Pacific and West Atlantic populations constitute a single species by analyzing nuclear and mitochondrial DNA sequence data. We found numerous fixed genetic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 24 publications
2
54
1
1
Order By: Relevance
“…This condition might be due to no genetic exchange between those two islands because seeds transportation mainly tends to occur on the island. This result was also similar to another part of Craig et al (2007) and Craig et al (2009) studies in two reef fish species where significant genetic differences were found among large geographically separated populations. Moreover, strong genetic structures were also observed among geographically separated cyprinids populations (Durand et al, 2002) and among Orizyas latipes populations Takehana et al (2003).…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…This condition might be due to no genetic exchange between those two islands because seeds transportation mainly tends to occur on the island. This result was also similar to another part of Craig et al (2007) and Craig et al (2009) studies in two reef fish species where significant genetic differences were found among large geographically separated populations. Moreover, strong genetic structures were also observed among geographically separated cyprinids populations (Durand et al, 2002) and among Orizyas latipes populations Takehana et al (2003).…”
Section: Resultssupporting
confidence: 77%
“…This value indicates that the used marker has a low level of polymorphisms. Low genetic polymorphisms were also observed in Myripristis berndti (Craig et al, 2007) and in Ephinepenlus itijara (Craig et al, 2009). This similar result indicates that low level of genetic polymorphisms can be observed in the broad scope of fish species.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…It was subsequently determined that goliath groupers in the Pacific constitute a cryptic species (E. quinquefasciatus) in comparison with the populations of the Atlantic (E. itajara), as demonstrated by their cytochrome B sequences (Craig et al 2009). Silva-Oliveira et al (2012), Seyoum et al (2013) and Silva-Oliveira et al (2014) developed specific markers for E. itajara to establish a more effective database for population studies with evolutionary models aimed specifically at the protection of the species.…”
Section: Introductionmentioning
confidence: 99%